Imiquimod-induced ROS production causes lysosomal membrane permeabilization and activates caspase-8-mediated apoptosis in skin cancer cells. Issue 3 (September 2022) - Chang, Shu-Hao; Lin, Pei-Ying; Wu, Tsai-Kun; Hsu, Chien-Sheng; Huang, Shi-Wei; Li, Zheng-Yi; Liu, Kuang-Ting; Kao, Jun-Kai; Chen, Yi-Ju; Wong, Tak-Wah; Wu, Chun-Ying; Shieh, Jeng-Jer
Abstract: Background: Lysosomal cell death is induced by lysosomal membrane permeabilization (LMP) and the subsequent release of lysosomal proteolytic enzymes, including cathepsins (CTSs), which results in mitochondrial dysfunction and apoptosis. Imiquimod (IMQ), a synthetic TLR7 ligand, has both antiviral and antitumor activity against various skin malignancies in clinical treatment. Previously, we demonstrated IMQ not only caused lysosomal dysfunction but also triggered lysosome biogenesis to achieve lysosomal adaptation in cancer cells. Objective: To determine whether lysosomes are involved in IMQ-induced apoptosis. Methods: The human skin cancer cell lines BCC, A375 and mouse melanoma cell line B16F10 were used in all experiments. Cell death was determined by the Cell Counting Kit-8 (CCK-8) assay and DNA content assay. Protein expression was determined by immunoblotting. Caspase-8 activity was assessed using a fluorescence caspase-8 kit and determined by flow cytometry and confocal microscopy. Results: IMQ not only induced lysosome damage but also abrogated lysosome function in skin cancer cells. IMQ-induced caspase-8 activation contributed to the processes of lysosomal cell death. Moreover, the use of ROS scavengers significantly abolished caspase-8 activation and inhibited IMQ-induced LMP. Additionally, pharmacological inhibition of CTSD not only abrogated caspase-8 activation but also rescued IMQ-induced cell death. Finally, lysosome-alkalizing agents enhanced the cytotoxicity of IMQ in vitro and in vivo. Conclusions: IMQ-induced ROS accumulation promotes LMP, releases CTSs into the cytosol, stimulates caspase-8 activation and finally causes lysosomal cell death. Lysosomal cell death and the CTSD/caspase-8 axis may play a crucial role in IMQ-induced cell death. Highlights: IMQ causes lysosomal membrane permeabilization and CTSs releasing into cytosol in skin cancer cells. IMQ induces lysosomal cell death which is mediated by CTSD/caspase-8 axis. IMQ-induced ROS generation is crucial for IMQ-induced caspase-8 activation and lysosomal cell death. Combination treatment with lysosome-alkalinizing agents and IMQ enhances anti-tumor response in skin cancer cells.